Female‐specific resource limitation does not make the opportunity for selection more female biased. (1st December 2020) - Martinossi‐Allibert, Ivain; Liljestrand Rönn, Johanna; Immonen, Elina
Abstract: Competition for limiting resources and stress can magnify variance in fitness and therefore selection. But even in a common environment, the strength of selection can differ across the sexes, as their fitness is often limited by different factors. Indeed, most taxa show stronger selection in males, a bias often ascribed to intense competition for access to mating partners. This sex bias could reverberate on many aspects of evolution, from speed of adaptation to genome evolution. It is unclear, however, whether stronger opportunity for selection in males is a pattern robust to sex‐specific stress or resource limitation. We test this in the model species Callosobruchus maculatus by comparing female and male opportunity for selection (i) with and without limitation of quality oviposition sites, and (ii) under delayed age at oviposition. Decreasing the abundance of the resource key to females or increasing their reproductive age was challenging, as shown by a reduction in mean fitness, but opportunity for selection remained stronger in males across all treatments, and even more so when oviposition sites were limiting. This suggests that males remain the more variable sex independent of context, and that the opportunity for selection through males is indirectly affected by female‐specific resource limitation.